A comparative study on the NOx storage and reduction performance of Pt/Ni1Mg2Al1Ox and Pt/Mn1Mg2Al1Ox catalysts. Issue 13 (12th November 2019) - Zhang, Cheng; Gao, Yanshan; Altaf, Naveed; Wang, Qiang
Abstract : Ni1 Mg2 Al1 O x, Mn1 Mg2 Al1 O x, 0.5Pt/Ni1 Mg2 Al1 O x and 0.5Pt/Mn1 Mg2 Al1 O x catalysts were prepared and their NSR performance was systematically investigated. Abstract : A series of Ni1 Mg2 Al1 O x, Mn1 Mg2 Al1 O x, 0.5Pt/Ni1 Mg2 Al1 O x and 0.5Pt/Mn1 Mg2 Al1 O x catalysts were carefully prepared and their NO x storage and reduction (NSR) performance including NO x oxidation efficiency (NOE), NO x storage capacity (NSC), NO x conversion rate (XNO ), N2 selectivity (SN2 ), N2 O selectivity (SN2 O ) and NH3 selectivity (SNH3 ), was systematically investigated. A SO2 resistance test was also performed in the presence of 100 ppm SO2 . The NOE and NSC experimental results revealed that the Ni1 Mg2 Al1 O x catalyst possesses a higher NSC, while the Mn1 Mg2 Al1 O x catalyst possesses a better NOE. With regard to XNO, 0.5Pt/Ni1 Mg2 Al1 O x presented higher results at 200 °C and 400 °C, while 0.5Pt/Mn1 Mg2 Al1 O x obtained the highest result at 300 °C, which was more than 60% for both. In addition, compared to 0.5Pt/Ni1 Mg2 Al1 O x, 0.5Pt/Mn1 Mg2 Al1 O x exhibited a relatively higher SN2 and lower SN2 O and SNH3 . The NO x -TPD and H2 -TPSR results indicated that NO x adsorbed on Ni1 Mg2 Al1 O x and 0.5Pt/Ni1 Mg2 Al1 O x is more stable, and that NH3 can be formed in large amounts in a lower temperature range. Both Pt-containing catalysts presented a quite stable XNO in ten cycles in the presence of 100 ppm SO2, and their SN2 can be remarkably enhanced to more than 80%, which could be attributed to the reactions of NH3 -SCR and SO2 + NH3 . We believe this new insight can provide a new way of thinking for the development of NSR catalysts.